A educação no contexto da globalização: migrações e direitos humanos - José Marín (Universidade do Vale do Rio dos Sinos (UNISINOS), 2008)
To examine education in respect of migration and human rights it is necessary to situate education in a global historical and political macro context. We are therefore presenting a reflection of globalisation and the challenges faced by education from a cross-cultural perspective. The good intentions expressed in the rhetoric of international organisations do not materialise in reality. The significant difference which exists in the quality of education between rich and poor nations is one of the main reasons provoking migration. The intercultural perspective provides the possibility to question the dominant universal knowledge and to accept the existence of plural knowledges. The cultural diversity of knowledge, beliefs and world visions must be considered in the context of biodiversity. Education emerges as a fundamental question in the hope of sections of civil society that can be regrouped under the term alter-globalisation which proposes the construction of a better world.